Penerapan Algoritma K-Nearest Neigbour Dalam Rekrutmen Pegawai Tidak Tetap Di BPJS Kesehatan Cabang Gunungsitoli - Satriyo Wibowo; Adli Abdillah Nababan (Pustaka Timur Publisher, 2021)
The selection of new employees is an initial process before the employee and the company enter into a cooperation contract. Selecting manually or without digitizing will harm the company in terms of accuracy and time efficiency. On that basis, the author feels that it is necessary to create a system to determine the application criteria to pass the administration so that they can follow the next process. There are many techniques to improve the accuracy of decisions that can be used, one of which is by using so as to increase the accuracy of the decisions taken. One of the algorithms used is the K-Nearest Neighbor (KNN) algorithm. The application of the K-Nearest Neighbor Method into a Data Mining which is used as an application that can predict the graduation of the temporary employees BPJS Kesehatan Recruitment, Gunung Sitoli by adjusting the criteria and using weights so that it can be used with this method.